Penerapan Algortima Genetika Dalam Sistem Penjadwalan Mata Pelajaran Di SD Islam Terpadu Darussalam - Syahputra, Adimas Ambang; Zulkarnain, Ismail Abdurrozzaq; Raharjo, Andy Triyanto Pujo (Universitas Multi Data Palembang, 2024)
Scheduling is an effort to manage time for activities to ensure their smoothness and continuity. One critical area is the scheduling of subjects at SD Islam Terpadu Darussalam. Manual scheduling is considered ineffective because it requires high accuracy to avoid conflicts and is lengthy and time-consuming. To address this issue, a scheduling system utilizing genetic algorithms for automation is needed. This research employs the waterfall method, consisting of four main stages: requirement analysis, system design, implementation, and testing. This method provides a clear structure and minimizes errors in the final stages. The scheduling system trials showed the most effective time was 00:12:30 with a population size of 10, Pm 0.2, and Pc 0.5. The web-based scheduling information system using a genetic algorithm allows subject scheduling to be accurate, fast, efficient, and effective at SD Islam Terpadu Darussalam. Additionally, an innovation involving email notifications sent 10 minutes before the next lesson begins can ensure teachers and students are better prepared, making the teaching and learning process smoother and more efficient.